PENGARUH EARNING PER SHARE, DEBT TO EQUITY RATIO, RETURN ON EQUITY, DAN PRICE TO BOOK VALUE TERHADAP RETURN SAHAM Studi Kasus Pada Perusahaan Industry Food and Beverages yang Terdaftar di Bursa Efek Indonesia - Suherman, Suherman; Siburian, Anwar (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
This research was to determine the effect of earning per share, debt to equity ratio, return on equity and price to book value toward stock return. The sample study is company on food and beverages industry are listed in Indonesia Stock Exchange in 2007-20010. Study sample as many as 17 companies food and beverages, where the method used was purposive sampling. Analysis of data using panel data regression, preceded by a test consisting of the assumption of classical test for normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Test data is done using panel data and for testing hypotheses using t test. The results of this analysis that the earnings per share and price to book has no significant relationship to the company's stock return, but the debt to equity ratio and return on equity have a significant effect on the company's stock return food and beverages industry. Keywords: Earnings Per Share, Debt to Equity Ratio, Return on Equity, Price to Book Value.